The Florida Agricultural Handbook of Solid and Hazardous Waste Regulation: Glossary - Michael T. Olexa; Damian Adams; Kathleen Maurer (EDIS)
Circular 1139, a multi-part handbook by Michael T. Olexa and Ian Goldfarb, helps Floridians recognize which agricultural and household activities may involve solid and hazardous wastes. It also provides an introduction to the agencies and statutes that govern solid and hazardous waste disposal. Published by the UF Department of Food and Resource Economics,  December 2013.